The Effect of Black Rice Extract on Lipid Profile Changes in Hypercholesterolemic Mus musculus - Awalia, Awalia; Makmun, Armanto; Bamahry, Aryanti R.; Rasfayanah, Rasfayanah; Mangarengi, Yusriani (Journal La Medihealtico, 2025)
Increased levels of lipid profiles in the blood affect the occurrence of coronary heart disease. Several large studies have shown that several natural food ingredients rich in antioxidants are associated with a lower incidence of cardiovascular disease. prevent the occurrence of several degenerative diseases. The research design used was a research design with a control group (pretest-posttest control group design). The research design used was a pretest-posttest control group design with 27 mice (mus musculus). They were divided into 3 groups: the negative control group (placebo), the positive control group (simvastatin), and the treatment control group (black rice). The intervention was carried out for 21 days. Data analysis was carried out using the paired T test and one way ANOVA test. Giving black rice extract can significantly improve lipid profile levels in mice, especially increasing HDL cholesterol levels by (10.44%) and decreasing triglyceride levels by (12.89%) as well as Simvastatin administration can also improve lipid profile levels significantly, especially decreased total cholesterol levels by (24.67%) and decreased LDL cholesterol by (32.08%). Based on the one way ANOVA test, P values were obtained successively in the administration of black rice extract, namely total cholesterol (p=<0.001), HDL cholesterol (p=<0.001), LDL cholesterol (p=<0.001), and triglycerides (p=<0.001). Likewise, in the administration of simvastatin, the lipid profile levels were obtained (p = <0.001). The conclusion of this study was that there was a significant effect of giving black rice extract on the lipid profile of hypercholesterolemia mice which was as effective as simvastatin.